To Determine the Plasma Levels of Malondialdehyde in Patient with Pre-eclampsia and Healthy Pregnant Women of Hyderabad, Sindh - Farheen Shaikh; Sanum Ali Dahri; Ali Raza Memon; Ayaz Ali Memon; Muhammad Yousuf Memon; Giran Naz Jagirani (JLUMHS, 2018)
OBJECTIVES: Pre-eclampsia is leading cause of maternal mortality and morbidity throughout the world. In Pakistan the mortality rate of pregnancy related problems is estimated to be approximately 500 per 100,000 live births. According to several studies oxidative stress and production of free radicles may be responsible for abnormal development of placenta results in the pathogenesis of pre-eclampsia. During oxidative stress Malondialdehyde has been proposed as novel factors concerned in development of pre-eclampsia. METHOD: Total 210 voluntaries were taken for the study, from which 50 voluntaries were normotensive healthy pregnant women as a control, 160 were patient with pre-eclampsia as cases. The subjects were recruited after taking obstetric history, anthropometric and clinical data. After taking informed consent, blood sample collected and stored for biochemical analysis. Malondialdehyde was analyzed on spectrophotometer. The study was conducted in Biochemistry Department Liaquat University of Medical & Health Sciences, Jamshoro from February 2015 to October 2015. RESULTS: Two hundred and ten subjects were included in this study. The Mean ± S.D of age of controls and pre-eclamptic subjects were noted as 27.5 ±4.5 and 27.38 ±4.3 years. Gestational ages of controls were 25.76 ±4.35 and cases were noted as 27.37 ±4.49 (p <0.053). The mean difference of serum Malondialdehyde levels in controls were 1.54 ±0.28 nmol/dl, while in pre-eclamptic subjects it was 2.42 ±0.63 nmol/dl which is highly significant and p <0.05 respectively. CONCLUSION: Malondialdehyde is index marker of lipid peroxidation. Increased formation of free radicles due to increased concentration of Malondialdehyde may put forward the possible involvement in the pathology of PE. The aim of this study to protects the mothers as well as her coming newborn from such life threatening disease.